THE NEW TESTAMENT AND HERMENEUTICS - Morgan, Robert (Journal of Dharma, 1980)
In the twenty-seven writings of the New Testament the Christian Church possesses a collection of documents from the first hundred years or so of its existence, which it uses alongside some older, mostly pre-Christian writings as its Scripture. In this context hermeneutics concerns the interpretation of these documents within this religious community. Although the Church has never used the New Testament in isolation from the Old, the question of its interpretation can be treated separately provided one remembers that for Christians its central subject-matter is the God of Israel who is held to have decisively intervened in and on behalf of his world in the life, death and resurrection of Jesus.